Sistema eólico de pequeno porte para interligação à rede elétrica - Reis, Mônica Magalhães (2008)
This work presents a wind energy system that employs a permanent magnet generator associated with a semicontrolled rectifier with reduced conduction losses. Additionally, a single-phase PWM inverter is used to connect the rectifier to the power grid. The rectifier, rated at 5 kW, has an input voltage of 220 V, with variable frequency operation. The inverter output voltage is 220 V, the frequency is 60 Hz and the output power is 5 kW. The rectifier provides high power factor by using hysteresis control. On the other hand, the inverter is modulated with double hysteresis control, which provides low THD of the current injected to the grid. The prominent characteristics of the aforementioned system are low cost, simplicity, and robustness. The theoretical analysis, design methodology, simulation results, and experimental results of the rectifier and inverter prototypes, both rated at 5 kW, are presented to validate the operating principle of the system.